Uji Potensi Buah Cempedak dan Nanas Sebagai Feromon Nabati dan Feromon Sintetis Terhadap Hama Kumbang Tanduk (Oryctes rhinoceros L) Pada Tanaman Kelapa Sawit - Armando, Aldi; Hayata, Hayata; Meilin, Araz (Universitas Batanghari, 2025)
There is potential for chempedak and pineapple fruits as a pheromones in controlling rhinoceros beetle pests on oil palm plants. This research was conducted in Marga Mulya and Panca Mulya Villages, Sungai Bahar District, Muaro Jambi Regency, in August - October 2024. This study aimed to determine the potential of cempedak and pineapple fruits as plant pheromones in controlling rhinoceros beetle pests on oil palm plantations. This research was analyzed descriptively. The parameters observed were the attacks percentage, the attacks intensity and the caught number of Oryctes rhinoceros. The results showed that there was an attack of Oryctes rhinoceros pests in Marga Mulya Village with the 5,38% as ahighest percentage of attacked plants and the lowest reaching 1,66%, the lowest attack intensity reaching 2,30% with a very light category. Meanwhile, in Panca Mulya Village, this attacks percentage reached 16,08% andit was 11,88% a lowest percentage, the attack intensity reached 5.33% with had a light category. Still not effective pineapple and chempedak fruit as pheromones.